Analysis of Damage to the Induce Draft Fan Component at PLTU PT. XYZ - Wilarso, Wilarso; Awang Surya; Asep Saepudin; Muhamad Ali Pahmi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Damage to the Induce Draft Fan (IDF), will impact to the combustion system which serves to provide Secondary Air to meet the air needs of the combustion system in the furnace in the boiler. There are 2 IDFs in the generating unit which are operated simultaneously or alternately. The purpose of this research is to determine the damage to the IDF so that there is no decrease in power supply to PLN generators. The method used in this study used fishbone analysis. Based on the analysis, the IDF damage occurs due to abrasion on the fan blade which is caused by the blade surface in contact with the abrasive material (Fe2O3) on the flue gas. The malfunctioning of the Electrostatic Precipitator (ESP) causes the abrasive material (Fe2O3) in the flue gas to not flow to the IDF, thus damaging the blade